Clinical outcomes of mechanical thrombectomy for acute ischemic stroke with large vessel occlusion: Insights from an Eastern Thailand mechanical thrombectomy center - Takong, Wittawat; Buranakul, Nattakarn; Puengcharoen, Sirinat; Boonyawan, Benjamas; Chaiwong, Warut (The ASEAN Journal of Radiology, 2025)
Background: Mechanical thrombectomy (MT) is the standard treatment for acute ischemic stroke with large-vessel occlusion (LVO), but regional data from Thailand are limited, particularly regarding factors influencing long-term outcomes. Objective: To evaluate 90-day functional independence (modified Rankin Scale [mRS] ≤2) after MT at a single center in Eastern Thailand and identify predictors of functional independence. Materials and Methods: We retrospectively analyzed all MT procedures from March 2019 to December 2023 at Bangkok Pattaya Hospital. Inclusion followed AHA guidelines and DAWN criteria, with adjustments for early presentations. Baseline demographics, imaging, angiography, and procedural data were collected. The primary endpoint was functional independence at 90 days. Associations were examined using univariate and multivariable logistic regression. Results: Of 141 MT cases, 132 were included (mean age 64.2 years; 87.8% Thai). Anterior circulation strokes accounted for 87.9%. Successful reperfusion (mTICI ≥2b) occurred in 81.1%, and functional independence at 90 days in 70.5%. Lower baseline NIHSS showed borderline association with functional independence (p=0.059). Post-procedural aICH or no ICH significantly reduced odds of functional independence compared with sICH (aICH: OR 0.09, 95% CI 0.02-0.45, p=0.006; no ICH: OR 0.05, 95% CI 0.01-0.20, p<0.001). Age, sex, atrial fibrillation, onset-to-recanalization time, and first-pass success were not significant predictors. sICH was more frequent with IVT+MT than MT alone (17.4% vs. 1.6%, p=0.006). Conclusion: MT at our center achieved high reperfusion and functional independence rates comparable to international benchmarks. Hemorrhagic transformation was a strong predictor, whereas age, sex, and treatment strategy were not. Careful imaging selection and individualized bridging therapy may optimize outcomes.